The lucky ones : one family and the extraordinary invention of Chinese America - Ngai, Mae M. (Princeton University Press, 2010)
Traces three generations of a Chinese-American family from its patriarch's self-invention as an immigration broker in post-gold rush San Francisco to the family's intimate involvement in the 1904 World's Fair.